Isolation of meyerozyma caribbica, penicillium georgiense, and pichia kudriavzevii from harumanis mango (mangifera indica l.) - Siti Munirah, Musa; L.M., Bakar; Jayabalan, Jeyakirtana; Muhammad Ikhmal, Rosali; Hajar Fauzan, Ahmad (2022)
Microbes from the environment usually spoil fruits. Thus, this study was carried out to study fungi that play an important role in rot fruits. Several microbes were isolated using the culturedependent method, Penicillium georgiense, Meyerozyma caribbica, and Pichia kudriavzevii. All these gDNA extracted can be identified with their characteristic pathogenic properties or benefits through high-throughput sequencing technology and compared from the NCBI database's known sequence. This finding can be explored further in the future with further experimental validation processes.